How Internal Marketing Drives Employees’ Internal Relationship Quality of Service Organizations Between Mainland China and Taiwan: The Moderating Roles of Internal Relationship Investment and Leader-Member Exchange - Li, Yunhe; Xiong, Minghua; Chang, Wei-Hsuan; Li, Ling (Frontiers in Psychology, 2021)
Recently, issues of human resource management gradually attract a lot of attention from organizational behavior scholars, thus how to effectively improve service employees’ job attitude and performance to meet the needs of stakeholders is one of the key issues in internal marketing. Based on the perspective of internal marketing, the study transforms the relevant factors applied to maintaining external customer relations into internal employee-oriented factors, so as to increase the understanding of the relationship between internal service recovery and internal relationship quality (IRQ). This study aims to explore (1) whether internal service recovery enhances IRQ; (2) whether internal relationship investment (IRI) positively moderates relationship between internal service recovery and IRQ; and (3) whether effectiveness of internal service recovery differentiates under different exchange relationship (high/low quality leader-member exchange). In this study, a total of 206 Mainland China and 250 Taiwanese participants were collected. In this study, a variance-based structural equation modeling (PLS-SEM) was performed to test the proposed hypothesizes and conduct comparative analysis. Empirical results in both samples show that internal service recovery has positive and significant effects on IRQ; internal relationship investment and leader-member exchange (LMX) positively and significantly moderate the relationship between internal service recovery and IRQ. Finally, based on the results, this study provides some discussions, suggestions and managerial implications for future studies in organizational management.